L’école musulmane algérienne de Ibn Bâdîs dans les années 1930, de l’alphabétisation de tous comme enjeu politique - Charlotte Courreye (Revue des Mondes Musulmans et de la Méditerranée)
The educational action of the Association of Algerian Muslim Ulamas in the 1930s, and particularly of his leader Ibn Bâdîs, has been characterized by the development of schools teaching religious sciences as well as elementary secular sciences. The defence of Arabic language and Islam in colonial context gave a particularly political dimension to their action. This went to a climax in 1938 when the French government enacted a decree attacking the Koranic schools, decree against which Ibn Bâdîs lead the struggle. The aim of Ibn Bâdîs’ teaching, in a large extend, from the madrasa to the nadi and from theatre to sports, was not only to help disseminating the Ulamas’ religious conceptions (iṣlâḥ) but also to unite Algerian Muslims by means of a common culture. It thus targeted a large audience, including children and adults, from various social classes – despite their alleged elitist culture – aiming at forming the Algerian Muslim umma.